2016
DOI: 10.1515/hsz-2015-0263
|View full text |Cite
|
Sign up to set email alerts
|

The intact Kunitz domain protects the amyloid precursor protein from being processed by matriptase-2

Abstract: Proteolytic processing of the amyloid precursor protein (APP) leads to amyloid-β (Aβ) peptides. So far, the mechanism of APP processing is insufficiently characterized at the molecular level. Whereas the knowledge of Aβ generation by several proteases has been expanded, the contribution of the Kunitz-type protease inhibitor domain (KPI) present in two major APP isoforms to the complex proteolytic processing of APP is poorly understood. In this study, we have identified KPI-containing APP as a very potent, slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Two examples are shown in Figure 6D. Alternative splicing of Amyloid precursor-like protein 2 ( Aplp2 ) is known to regulate inclusion of a bovine pancreatic trypsin inhibitor (BPTI) Kunitz domain (Sandbrink et al, 1997) and this domain is known to regulate proteolysis of the related protein APP, the amyloid precursor protein implicated in Alzheimer’s disease (Beckmann et al, 2016). Differential inclusion of this exon is known to occur between neurons and nonneurons.…”
Section: Resultsmentioning
confidence: 99%
“…Two examples are shown in Figure 6D. Alternative splicing of Amyloid precursor-like protein 2 ( Aplp2 ) is known to regulate inclusion of a bovine pancreatic trypsin inhibitor (BPTI) Kunitz domain (Sandbrink et al, 1997) and this domain is known to regulate proteolysis of the related protein APP, the amyloid precursor protein implicated in Alzheimer’s disease (Beckmann et al, 2016). Differential inclusion of this exon is known to occur between neurons and nonneurons.…”
Section: Resultsmentioning
confidence: 99%
“…Matriptase‐2 is a member of the type II transmembrane serine proteases (TTSPs), an understudied group of 17 membrane‐bound serine proteases (Szabo & Bugge, ), and has been reported to shed APP within the amyloid β domain, at least in transfected cells or in vitro (Beckmann et al , ). Other TTSPs appear to cleave predominantly soluble proteins or activate membrane‐bound proteins, but without shedding them in their juxtamembrane domains (Jackle et al , ; Murray et al , ).…”
Section: Hardware: Canonical Sheddasesmentioning
confidence: 99%
“…If this proteolytic interaction may have impact on neurodegenerative disorders has to be shown. Surprisingly, however, in a different study MT-2 was found to directly cleave neuronal APP695, but was effectively inhibited by the Kunitz protease inhibitor (KPI) domain present in other APP isoforms (APP751 and APP770) from the periphery (Beckmann et al, 2016). Of note, the additional domains in APP751 (KPI) and APP770 (KPI/OX2) do not lead to altered proteolytic processing by meprin β (Jefferson et al, 2011).…”
Section: Activationmentioning
confidence: 99%